Studies on zooplankton of Lago Paione Superiore - Patrizia COMOLI; Marina MANCA (Journal of Limnology, 1999)
We report here the results of a three year study on the zooplankton of Lago Paione Superiore, an acid sensitive lake above the tree line in the Italian Alps. The research was carried out within MOLAR, an EC-founded Project on “Measuring and Modeling the dynamic response of remote mountain lakes ecosystems to environmental change”. This study comes after a series of investigations on the effects of acidification, in which we documented the changes occurred with decreasing water pHs, by comparing the recent situation with that in the literature of the 40s, and reconstructed the beginning of anthropogenic disturbance through an analysis of the past cladocera assemblages archived in the lake sediments. A characteristic pattern in seasonal periodicity is a transition from a community dominated by small zooplankton (August) to a community where the large particle-feeder Daphnia longispina dominates. This is a typical pattern observed in fishless, copepod-cladocera lakes. Regardless from which food is able to exploit, Daphnia population of Lago Paione Superiore is composed by well-fed organisms, visually rich in lipids, able to produce more than one generation/ year of parthenogenetic females at density levels which are rather high in an oligotrophic high mountain lake.